Lysophosphatidic Acid and Ion Channels as Molecular Mediators of Pain - Juárez-Contreras, Rebeca; Rosenbaum, Tamara; Morales-Lázaro, Sara L. (Frontiers in Molecular Neuroscience, 2018)
Lysophosphatidic acid or LPA is a phospholipid which has been extensively linked to the generation and maintenance of pain. Several ion channels have also been shown to participate in this pathological process but the link between LPA and these proteins in pain has just recently gained interest. In this respect, the field has advanced by determining the molecular mechanisms by which LPA promotes changes in the function of some ion channels. While some of the actions of LPA include modulation of signaling pathways associated to its specific receptors, other include a direct interaction with a region in the structure of ion channels to affect their gating properties. Here, we focus on the known effects of LPA on some transient receptor potential, sodium, potassium and calcium channels. As the field moves forward, mechanisms are unveiled with the hope of understanding the underlying causes of pain in order to target these and control this pathophysiological state.